Molecular Design of Mesoporous NiCo2O4and NiCo2S4with Sub-Micrometer-Polyhedron Architectures for Efficient Pseudocapacitive Energy Storage - Liu, Y.; Wang, Z.; Zhong, Y.; Tade, Moses; Zhou, W.; Shao, Zongping (Wiley, 2017)
© 2017 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim Spinel-type NiCo 2 O 4 (NCO) and NiCo 2 S 4 (NCS) polyhedron architectures with sizes of 500–600 nm and rich mesopores with diameters of 1–2 nm are prepared facilely by the molecular design of Ni and Co into polyhedron-shaped zeolitic imidazolate frameworks as solid precursors. Both as-prepared NCO and NCS nanostructures exhibit excellent pseudocapacitance and stability as electrodes in supercapacitors. In particular, the exchange of O 2- in the lattice of NCO with S 2- obviously improves the electrochemical performance. NCS shows a highly attractive capacitance of 1296 F g -1 at a current density of 1 A g -1 , ultrahigh rate capability with 93.2% capacitance retention at 10 A g -1 , and excellent cycling stability with a capacitance retention of 94.5% after cycling at 1 A g -1 for 6000 times. The asymmetric supercapacitor with an NCS negative electrode and an active carbon positive electrode delivers a very attractive energy density of 44.8 Wh kg -1 at power density 794.5 W kg -1 , and a favorable energy density of 37.7 Wh kg -1 is still achieved at a high power density of 7981.1 W kg -1 . The specific mesoporous polyhedron architecture contributes significantly to the outstanding electrochemical performances of both NCO and NCS for capacitive energy storage.